A numerical study of the side-wall effects on turbulent bands in channel flow at transitional Reynolds numbers. (30th May 2022) - Wu, Haoyang; Song, Baofang
Abstract: We investigated the side-wall effects on turbulent bands in channel flow at transitional Reynolds numbers by direct numerical simulations using the open source spectral-element code Nektar++. The width-to-height aspect ratio of 50:1 is considered for this study. Our study shows that turbulent bands can survive the collision with the side wall above bulk Reynolds number of R e ≃ 1000 but decay below R e ≃ 975, i.e. the critical Reynolds number should be approximately between the two Reynolds numbers. We also discussed about the underlying mechanism for the decay of the band at low Reynolds numbers and potential effects of larger spanwise channel widths than that considered in our study. The results are informative for experimental studies of channel flow turbulence at transitional Reynolds numbers. Highlights: The collision between turbulent bands and channel side wall was studied. A forcing technique for generating turbulent bands was implemented in Nektar++. Results show that turbulent bands cannot survive the collision at R e ≲ 975 . Turbulence can survive the collision above R e ≃ 1000 . We proposed a mechanism for the decay of turbulent bands at low Reynolds numbers. The side-wall effects should be taken care of at low Reynolds numbers in experiments.